Conflict of Interest; Blind Spots at the Research Field - Mohammadreza Amiresmaili; Khalil Kalavani (Health, Spirituality and Medical Ethics, 2021)
"Conflict of interest" or "competing interest" occurs when the author or sponsor of the study has a financial, commercial, legal, or professional relationship with the organization, individuals, study samples, or research environment, so as the results of that study are influenced. When the authors of a study seek to publish research, they must fully disclose what was mentioned above. Conflicts of interest can occur both financially and non-financially. In some cases, non-financial conflicts of interest are even more important than financial ones. Such conflicts originate from personal, political, academic, ideological, or religious issues (1). Although there is no single definition of conflict of interest in the scientific community, almost all reputable journals ask authors to disclose conflict of interest at the time of submitting their articles. However, various studies have shown that accurate disclosure of conflicts of interest is significantly rare (2-4).